Accurate transcription of truncated ribosomal DNA templates in a Drosophila cell-free system. - Kohorn, B D (1982)
An extract of Drosophila melanogaster Kc cells is shown to give specific and accurate transcription of truncated segments of cloned D. melanogaster ribosomal DNA (rDNA). When clones are digested with restriction enzymes so that the initiation site is flanked by 0.3 kilobase (kb) of nontranscribed spacer and greater than 0.4 kb of external transcribed spacer, RNA polymerase I activity in the extract parallels in vivo rRNA synthesis in selection of the coding strand of template and the site of transcription initiation. When greater than 0.3 kb of the nontranscribed spacer is contiguous with transcribed spacer, in vitro initiations evidently also occur in repeated sequences adjacent to the site of in vivo initiation; when less than or equal to 0.4 kb of the external transcribed spacer is present in a segment, expected transcripts are heterogeneous in length or not detectable. Transcription in the cell-free system requires the specific addition of D. melanogaster rDNA: neither D. virilis rDNA, vector plasmid, nor clones of D. melanogaster genes that are transcribed in vivo by RNA polymerases II and III serve as templates in the system. Drosophila rDNA units that have an interruption in the 28S rRNA coding region are not transcribed in vivo, but restriction digests of a recombinant phage DNA that contains such a unit are active as template for in vitro rDNA transcription.